2016
DOI: 10.1002/2015jd024297
|View full text |Cite
|
Sign up to set email alerts
|

Planning, implementation, and scientific goals of the Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC4RS) field mission

Abstract: The Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC4RS) field mission based at Ellington Field, Texas, during August and September 2013 employed the most comprehensive airborne payload to date to investigate atmospheric composition over North America. The NASA ER‐2, DC‐8, and SPEC Inc. Learjet flew 57 science flights from the surface to 20 km. The ER‐2 employed seven remote sensing instruments as a satellite surrogate and eight in situ instruments. The DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
245
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 183 publications
(249 citation statements)
references
References 85 publications
4
245
0
Order By: Relevance
“…We implemented this crude kinetic limitation of ammonia uptake by SNA aerosol into the GEOS-Chem chemical transport model (CTM) version 9-02, previously applied by Kim et al (2015) to simulation of aerosol observations from the NASA SEAC 4 RS aircraft campaign over the Southeast in summer-fall 2013 (Toon et al, 2016). The simulation includes detailed oxidant-aerosol chemistry as described by Kim et al (2015) and Travis et al (2016).…”
Section: Possible Mass Transfer Limitation By Organic Aerosol?mentioning
confidence: 99%
“…We implemented this crude kinetic limitation of ammonia uptake by SNA aerosol into the GEOS-Chem chemical transport model (CTM) version 9-02, previously applied by Kim et al (2015) to simulation of aerosol observations from the NASA SEAC 4 RS aircraft campaign over the Southeast in summer-fall 2013 (Toon et al, 2016). The simulation includes detailed oxidant-aerosol chemistry as described by Kim et al (2015) and Travis et al (2016).…”
Section: Possible Mass Transfer Limitation By Organic Aerosol?mentioning
confidence: 99%
“…NASA's Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS, Toon et al, 2016, https://espo.nasa.gov/ home/seac4rs/content/SEAC4RS) was conducted in AugustSeptember 2013. More than 20 research flights were executed, including 10 September DC-8 flights over the southeastern US primarily focusing on the attribution and the quantification of trace gas pollution and their distributions as a result of deep convection.…”
Section: Isoprene Measurementsmentioning
confidence: 99%
“…Observations of atmospheric methane reviewed by Brandt et al (2014) have implied that the US national inventory reported by the Environmental Protection Agency (EPA) may be greatly underestimated. Here we use aircraft observations from the NASA SEAC 4 RS aircraft campaign over the Southeast US (Toon et al, 2016), together with a newly gridded version of the EPA inventory , in a fine-resolution inversion with detailed error characterization to better quantify methane emissions over this major source region.…”
Section: Introductionmentioning
confidence: 99%